simplify (4root3-3root5)power2
Answers
Answered by
13
Heya ✋
Let see your answer !!!!
(4√3 - 3√5)^2
= (4√3)^2 + (3√5)^2 - 2 × 4√3 × 3√5
= 48 + 45 - 24√15
= 93 - 24√15
Thanks :)))))
Let see your answer !!!!
(4√3 - 3√5)^2
= (4√3)^2 + (3√5)^2 - 2 × 4√3 × 3√5
= 48 + 45 - 24√15
= 93 - 24√15
Thanks :)))))
Answered by
3
Here is the solution
![[4 \sqrt{3} -3 \sqrt{5} ]^{2} [4 \sqrt{3} -3 \sqrt{5} ]^{2}](https://tex.z-dn.net/?f=%5B4+%5Csqrt%7B3%7D+-3+%5Csqrt%7B5%7D+%5D%5E%7B2%7D+)
by using the identity
![[a-b]^{2}= a^{2}+ b^{2}-2ab [a-b]^{2}= a^{2}+ b^{2}-2ab](https://tex.z-dn.net/?f=+%5Ba-b%5D%5E%7B2%7D%3D+a%5E%7B2%7D%2B+b%5E%7B2%7D-2ab++)
we get
![= [4 \sqrt{3}] ^{2} + [3 \sqrt{5}] ^{2} -2[4 \sqrt{3}][3 \sqrt{5}] = [4 \sqrt{3}] ^{2} + [3 \sqrt{5}] ^{2} -2[4 \sqrt{3}][3 \sqrt{5}]](https://tex.z-dn.net/?f=%3D+%5B4+%5Csqrt%7B3%7D%5D+%5E%7B2%7D+%2B++%5B3+%5Csqrt%7B5%7D%5D+%5E%7B2%7D+-2%5B4+%5Csqrt%7B3%7D%5D%5B3+%5Csqrt%7B5%7D%5D++)
![= 48 + 45 -24 \sqrt{15} = 48 + 45 -24 \sqrt{15}](https://tex.z-dn.net/?f=%3D+48+%2B++45+-24+%5Csqrt%7B15%7D+)
![= 93 -24 \sqrt{15} = 93 -24 \sqrt{15}](https://tex.z-dn.net/?f=%3D+93+-24+%5Csqrt%7B15%7D+)
#Prashant24IITBHU
by using the identity
we get
#Prashant24IITBHU
Similar questions